PRDX1 Cys52Ser variant alleviates nonalcoholic steatohepatitis by reducing inflammation in mice - Zhonghao Bai; Wen Yin; Rui Liu; Minglei Tang; Xiaofeng Shi; Cheng Luo; Xiangyang Xie (Elsevier, 2023)
Objective: Peroxiredoxin 1 (PRDX1) is a peroxidase and guards against oxidative stress by scavenging intracellular peroxides, whereas it also has been shown to stimulate inflammatory response by functioning as a chaperone protein. The potential in vivo link between PRDX1's peroxidase activity and its pro-inflammatory activity remains elusive. Methods: We generated peroxidase-dead PRDX1 variant mice by mutating its peroxidatic cysteine at 52 (Cys52) to serine, here referred to as PRDX1Cys52Ser. Trx-TrxR-NADPH coupled activity assay was applied to evaluate the peroxidase activity of global PRDX in PRDX1Cys52Ser variant mice. PRDX1Cys52Ser mice and their wild-type littermates were subjected to western diet or methionine and choline deficient diet feeding. NASH phenotypes were assessed through different analyses including physiological measurements, immunohistochemical staining, and quantitative PCR (qPCR). RNA sequencing, qPCR and western blotting were used to reveal and validate any changes in the signaling pathways responsible for the altered NASH phenotypes observed between WT and PRDX1Cys52Ser variant mice. Results: PRDX1Cys52Ser variant mice showed impaired global PRDX peroxidase activity and reduced susceptibility to diet-induced NASH and liver fibrosis. Mechanistically, PRDX1 Cys52Ser variant suppressed NF-κB signaling and STAT1 signaling pathways that are known to promote inflammation and NASH. Conclusion: The peroxidatic Cys52 of PRDX1 is required for its pro-inflammatory activity in vivo. This study further suggests that PRDX1 may play dual but opposing roles in NASH.